1997
DOI: 10.1002/(sici)1096-9063(199711)51:3<299::aid-ps653>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Phenological adaptation in weeds-an evolutionary response to the use of herbicides?

Abstract: :The possibility of phenological adaptation in weed species is discussed in terms of an evolved response to herbicide use. Weed populations often exhibit heritable variation in life history traits that may reÑect phenological adaptations. Approaches to assessing "adaptednessÏ are discussed. Selection for seed dormancy in a grass weed is considered through life history analysis. It is concluded that too little is known about both life histories and Ðtness of weed species in varying environments for conclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…Mortimer (1997) indicated that one of the evolutionary responses used to avoid selection pressure from herbicides is the selection of individuals with deep dormancy; individuals that germinate later are more likely to complete their life cycle compared with those that have received herbicide application. Thus, with the disappearance of the selective factor, delayed germination may represent a disadvantage for the establishment of seedlings, which could cause the elimination of R plants and thus return of the population to the S state (Maxwell et al, 1990).…”
Section: Jesús R Torres-garcía Et Almentioning
confidence: 99%
“…Mortimer (1997) indicated that one of the evolutionary responses used to avoid selection pressure from herbicides is the selection of individuals with deep dormancy; individuals that germinate later are more likely to complete their life cycle compared with those that have received herbicide application. Thus, with the disappearance of the selective factor, delayed germination may represent a disadvantage for the establishment of seedlings, which could cause the elimination of R plants and thus return of the population to the S state (Maxwell et al, 1990).…”
Section: Jesús R Torres-garcía Et Almentioning
confidence: 99%
“…Reductions in the biological cycle of the Gto and Col 4 biotypes were observed and might be related to selection pressure on life history components in these populations. Changes in phenology also have been observed as an evolutionary response to adapt to agroecosystems, mainly in relation to the timing of the crop cycle (Duke 1985, Weinig 2005, Kawecki 2008) and in response to the application of herbicides and other cultural practices (Mortimer 1997). These characteristics could be an indicator that the biotypes Col 4 and Gto, in addition of being resistant, are also adapted to agricultural practices.…”
Section: Discussionmentioning
confidence: 99%
“…Dormancy and asynchronous germination are common traits in weeds, and they vary both among and within species. Since these traits are partly genetically determined, they may evolve in response to management practices . Therefore, a comprehensive understanding of the durability of herbicide‐based management strategies should consider not only the evolution of herbicide resistance, but also the evolution of phenological traits such as seed dormancy, and the likely interactions between phenological evolutions and the evolution of herbicide resistance.…”
Section: Introductionmentioning
confidence: 99%